2021
DOI: 10.3928/1081597x-20210225-02
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Corneal Epithelial Remodeling After Intracorneal Ring Segment Procedures for Keratoconus: An Optical Coherence Tomography Study

Abstract: PURPOSE: To assess epithelial corneal remodeling by anterior segment optical coherence tomography (AS-OCT) after intracorneal ring segments (ICRS) implantation in keratoconic eyes. METHODS: This prospective observational study included patients with keratoconus receiving ICRS of different arc lengths according to their tomographic pattern. AS-OCT and corneal topography (Scheimpflug camera) were performed before and 1, 3, and 6 months after surgery. Corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Thanks to its dedicated caliper tool, it also allowed us to accurately document changes by measuring the stromal thickness at the thinnest part. AS-OCT is an effective tool for systematic anterior-segment imaging, allowing the detailed detection of the front-to-back layered corneal structure for quantitative analysis and monitoring of the healing process (David et al, 2021). Using AS-OCT granted us quantitative monitoring of structural changes in NK treated by cenegermin, obtaining a better understanding of rh-NGF-driven corneal wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to its dedicated caliper tool, it also allowed us to accurately document changes by measuring the stromal thickness at the thinnest part. AS-OCT is an effective tool for systematic anterior-segment imaging, allowing the detailed detection of the front-to-back layered corneal structure for quantitative analysis and monitoring of the healing process (David et al, 2021). Using AS-OCT granted us quantitative monitoring of structural changes in NK treated by cenegermin, obtaining a better understanding of rh-NGF-driven corneal wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…They showed, by ultrasound imaging, that epithelial filling occurred in the concave anterior stromal groove produced after ICRS implantation for the treatment of myopia [ 22 ]. David et al analyzed SD-OCT results for nonasymmetric ICRS implantation (Ferrara type) for keratoconus and found significant epithelial thickening in the internal zones juxtaposed with the ICRS; they showed that this epithelial thickening differed between ICRS and keratoconus types [ 23 ]. The stroma of the cone apex also seems to be remodeled following ICRS implantation, as also shown by the thickening of the epithelium 23 , and could be the result of stromal flattening.…”
Section: Discussionmentioning
confidence: 99%
“…Reinstein et al showed that ICRS implantation for myopia treatment induced epithelial filling in the concave anterior stromal groove [ 22 ]. In anterior-segment optical coherence topography (AS-OCT) analyses on different types of keratoconus, David et al showed that epithelial thickening in the internal zones contiguous to a symmetric ICRS differed between ICRS types, and reported epithelial thinning above the ICRS, with no smoothing of this effect after six months of follow-up [ 23 ]. Analyses of epithelium remodeling after asymmetric ICRS implantation are useful for determining whether the cornea has been regularized by ICRS implantation and for analyses of the asymmetric stromal effect of the asymmetric ICRS.…”
Section: Introductionmentioning
confidence: 99%
“…13 The cycle of progressive focal weakening is interrupted by the improvement in curvature and increased thickness (induced by epithelial thickening adjacent to the ICRS to compensate for the ridge created with a thickening of the epithelium over the cone because of regularization of the stromal surface), and they tend to a mildly stiffer response with the structural support of the ICRS. 22 A recent study by Torres-Netto et al investigated the early biomechanical changes induced by ICRSs in ex vivo porcine eyes and showed a significantly effective change in modulus and increase in IOP measurement after ring implantation. 23 This is likely because of the difference in corneal response to load with the added structural support of the rings, similar to the current study, and not because of stiffening of the native tissue, as stated by the authors.…”
Section: Discussionmentioning
confidence: 99%